Iron-Catalyzed Alkene Hydroboration with Pinacolborane - Zhang, Lei; Huang, Zheng (Synlett, 2013)
Well-defined iron complexes have been studied intensively as an alternative for precious-metal catalysts in recent years. Here we highlight the opportunities of using iron complexes as catalysts in diene and alkene hydroboration. The iron complexes, supported by suitable ligands, can be superior to precious-metal systems in terms of efficiency and selectivity for alkene hydroborations with pinacolborane.
Keywords: iron; alkene; organoboronate ester; hydroboration; homogeneous catalysis